WORK ENVIRONMENT AS MODERATING VARIABLE IMPACT OF TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE (Equilibrium: Jurnal Ekonomi Syariah, 2022)
This study aims to determine the effect of transformational leadership on the work environment, the influence of organizational culture on the work environment, the influence of the work environment on work performance, the influence of transformational leadership on work performance through the work environment, and the influence of organizational culture on work performance through the work environment. Using quantitative methods with questionnaire data collection methods. The population in this study were all employees in the Non-Bank Islamic Financial Institutions, with a saturated sampling technique of 45 employees. Use path analysis with external model measurements, mediation tests, and internal model measurements. The results showed that transformational leadership had a significant positive effect on the work environment, organizational culture had a significant negative effect on the work environment, and the work environment had a significant positive effect on work performance. the work environment can mediate the influence of transformational leadership on work performance. Meanwhile, the work environment has not been able to mediate the influence of organizational culture on performance.